2020
DOI: 10.1111/1744-7917.12888
|View full text |Cite
|
Sign up to set email alerts
|

Hosting certain facultative symbionts modulates the phenoloxidase activity and immune response of the pea aphid Acyrthosiphon pisum

Abstract: The pea aphid Acyrthosiphon pisum hosts different facultative symbionts (FS) which provide it with various benefits, such as tolerance to heat or protection against natural enemies (e.g., fungi, parasitoid wasps). Here, we investigated whether and how the presence of certain FS could affect phenoloxidase (PO) activity, a key component of insect innate immunity, under normal and stressed conditions. For this, we used clones of A. pisum of different genetic backgrounds (LL01, YR2 and T3-8V1) lacking FS or harbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 84 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…While A. pisum LL01 and YR2 both have the obligatory symbiont Buchnera aphidicola which participates in their nutrition, only YR2 has a secondary symbiont Regiella insecticola that can provide the host with more resistance to biotic and abiotic stresses (temperature, parasitoid attack, etc.) 36 . The similar results of A. pisum LL01 and YR2 aphids indicate that despite the presence of the secondary symbiont, aphids are equally sensitive to the new stress caused by the CO 2 laser.…”
Section: Resultsmentioning
confidence: 99%
“…While A. pisum LL01 and YR2 both have the obligatory symbiont Buchnera aphidicola which participates in their nutrition, only YR2 has a secondary symbiont Regiella insecticola that can provide the host with more resistance to biotic and abiotic stresses (temperature, parasitoid attack, etc.) 36 . The similar results of A. pisum LL01 and YR2 aphids indicate that despite the presence of the secondary symbiont, aphids are equally sensitive to the new stress caused by the CO 2 laser.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a sequenced strain (32) of Regiella that was isolated from another aphid species (Myzus persicae strain .515) ( 18) is harbored at extremely low densities (more than an order of magnitude below other strains) but has been nonetheless transmitted vertically over many years of laboratory propagation. The aphid immune system has been implicated in the regulation of vertically-transmitted symbioses in several studies, with two related symbionts (Regiella insecticola and Hamiltonella defensa) leading to decreased expression of key insect innate immune system genes and fewer circulating immune cells (22)(23)(24)(25). We have also found that knocking down expression of Phenoloxidase using RNAi leads to increased Regiella density over aphid development (24).…”
Section: Discussionmentioning
confidence: 61%
“…The aphid immune system has been implicated in the regulation of vertically-transmitted symbioses in several studies, with two related symbionts ( Regiella insecticola and Hamiltonella defensa ) leading to decreased expression of key insect innate immune system genes and fewer circulating immune cells (22-25). We have also found that knocking down expression of Phenoloxidase using RNAi leads to increased Regiella density over aphid development (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression controlling gene is a tyrosinase gene. Tyrosinase in plants is called polyphenol oxidase, in insects, it is called phenol oxidase, and in eukaryotes and microorganisms, it is known as tyrosinase [32,33]. A large number of studies have confrmed that tyrosinase gene mutations can cause abnormal body color in a variety of animals (mice, rabbits, Oryzias latipes, etc.)…”
Section: Introductionmentioning
confidence: 99%